Ullmann's encyclopedia of industrial chemistry - Ullmann, Fritz. 1875-1939 (VCH, 1985)
ULLMANN'S Encyclopedia of Industrial Chemistry is the benchmark reference in chemistry and chemical and life science engineering, covering inorganic and organic chemicals, advanced materials, pharmaceuticals, polymers and plastics, metals and alloys, biotechnology and biotechnological products, food chemistry, process engineering and unit operations, analytical methods, environmental protection, and much more. Complete coverage of the science and technology in all areas of industrial chemistry. Fully international in scope and coverage, the contents have been compiled under the supervision of a renowned global Editorial Advisory Board. New and updated articles are added every two months. Contains over 1,000 major articles, written by some 3,000 authors who are experts in their fields and affiliated to leading chemical companies or research institutes. Breadth of knowledge - more than 16 million words, nearly 15,000 tables, 25,000 figures, and innumerable literature sources and cross-references. All the benefits of an online reference, including: searches using wildcards and Boolean operators and cross-reference hyperlinking.